2009
DOI: 10.1038/bmt.2009.267
|View full text |Cite
|
Sign up to set email alerts
|

Implications of CD34+ cell dose on clinical and haematological outcome of allo-SCT for acquired aplastic anaemia

Abstract: The precise effects of CD34 þ cell dose on the outcome of allogeneic transplantation for aplastic anaemia (AA) are not known. Previous studies have used the total mononuclear cell count to quantify stem cell dose. We evaluated the effects of CD34 þ cell dose on the clinical and haematological end points of transplantation. The transplant variables and outcome parameters on 46 patients with acquired AA were assessed by comparing low vs high CD34 þ cell doses. Infusion of less than 2 Â 10 6 /kg of CD34 þ cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…42,43 We have recently shown that infusion of Ͻ 2.0 ϫ 10 6 CD34 cells/kg is associated with increased graft failure, increased incidence of bacterial infections and delay in neutrophil engraftment, although neutrophil engraftment is more dependent on stem cell source. 28 One study reported more chronic GVHD when Ͼ 3.7 ϫ 10 8 nucleated cells/kg were infused, but data on CD34 cells were lacking. 44 We have shown in this study that the use of PBSC with alemtuzumab-based conditioning permits collection of an adequate cell dose without causing significant chronic GVHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 We have recently shown that infusion of Ͻ 2.0 ϫ 10 6 CD34 cells/kg is associated with increased graft failure, increased incidence of bacterial infections and delay in neutrophil engraftment, although neutrophil engraftment is more dependent on stem cell source. 28 One study reported more chronic GVHD when Ͼ 3.7 ϫ 10 8 nucleated cells/kg were infused, but data on CD34 cells were lacking. 44 We have shown in this study that the use of PBSC with alemtuzumab-based conditioning permits collection of an adequate cell dose without causing significant chronic GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…20,23,28,29 All patients were screened for CMV infections/ reactivation at least weekly for the first 3-6 months using CMV antigenemia or PCR-based assay.…”
Section: Supportive Carementioning
confidence: 99%
“…These analyses almost always showed that the best correlation is between committed progenitors and rapidity of hemato poietic reconstitution [5254] in comparison with total cells and CD34+ cells. Other studies have shown the absence of correlation between the total cell number, CD34+ number and clinical and hematologic outcomes [55] . This confirms a relative progenitor and stem cell source dependent value of these parameters [unfortunately, the progenitor (CFC) number analysis was not shown].…”
Section: Clinical Vs Experimentalmentioning
confidence: 99%
“…Evaluation of infused BM CD34? cell dose showed that the risk of graft failure increased significantly with doses of \2 9 10 6 /kg [36]. Thus, it is important to ensure an adequate stem cell dose, although data are lacking in terms of the optimal number of CD3?…”
Section: Early Studies Using Campath-1 Antibodies In Saa Hsctmentioning
confidence: 99%